Business cycle synchronisation in East Asia: The role of value‐added trade. (17th May 2018) - Jiang, Wei; Li, Yunong; Zhang, Shajuan
Abstract: We empirically investigate the relationship between business cycle synchronisation and the role of value‐added trade focusing on a panel of 12 Asian countries from 1995 to 2011. In addition, we propose the inclusion of two novel determinants, for example external value‐added trade intensity and exchange rate volatility and also saturate our empirical model with other common determinants found in the literature. Our findings first confirm that value‐added trade intensity, rather than gross trade intensity, has a sizable, positive and statistically significant impact on synchronisation among East Asian countries. Second, the exchange rate volatility has a significant negative effect on the business cycle synchronisation, which verifies that the exchange rate volatility is another important determinant of business cycle synchronisation. Our findings have important implications for the monetary cooperation in the region: strengthening trade linkage could reduce the costs of monetary cooperation by increasing the incidence of symmetric shocks.